2006
DOI: 10.1210/en.2005-1555
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Uterine Cell Death, Renewal, and Their Hormonal Regulation in Hamsters that Show Progesterone-Dependent Implantation

Abstract: This study was initiated to investigate the significance of uterine cell death and proliferation during the estrous cycle and early pregnancy and their correlation with sex steroids in hamsters where blastocyst implantation occurs in only progesterone-primed uteri. The results obtained in hamsters were also compared with mice where blastocyst implantation occurs in progesterone-primed uteri if estrogen is provided. Apoptotic cells in the uterus were detected by using terminal deoxynucleotide transferase-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 47 publications
2
50
2
Order By: Relevance
“…This luminal epithelial cell death is identified as apoptosis and is executed by Caspase 3, because a Caspase 3 inhibitor N-acetyl-DEVD-CHO inhibits implantation. 15 Opposite to our initial assumption that a premature decrease of epithelial polarity in the absence of Rac1 would lead to increased epithelial cell death, we found that Rac1 is essential for timely luminal epithelial degradation within the implantation chamber; its null mutation results in a persistent epithelial layer surrounding the implantation blastocyst even on day 6 of pregnancy. However, unlike previous observations in Klf5 null mice, 5 these retained epithelial layers in the Rac1 null implantation chamber is not due to a reduced Cox2 expression.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This luminal epithelial cell death is identified as apoptosis and is executed by Caspase 3, because a Caspase 3 inhibitor N-acetyl-DEVD-CHO inhibits implantation. 15 Opposite to our initial assumption that a premature decrease of epithelial polarity in the absence of Rac1 would lead to increased epithelial cell death, we found that Rac1 is essential for timely luminal epithelial degradation within the implantation chamber; its null mutation results in a persistent epithelial layer surrounding the implantation blastocyst even on day 6 of pregnancy. However, unlike previous observations in Klf5 null mice, 5 these retained epithelial layers in the Rac1 null implantation chamber is not due to a reduced Cox2 expression.…”
Section: Discussionmentioning
confidence: 62%
“…14 There is early evidence that Caspase 3 is an executor of uterine epithelial apoptotic death and loss of Klf5 in mice leads to impaired epithelial cell elimination at postimplantation. 5,15 However, it remained largely elusive regarding the underlying mechanisms governing luminal epithelial cell death after blastocyst-uterus attachment.…”
mentioning
confidence: 99%
“…Female hamsters that showed three consecutive estrous cycles were placed with fertile males on the evening of the proestrous day for mating. Microscopic finding of spermatozoa in the vaginal discharge the next morning was designated day 1 of pregnancy (Wang et al 2002, 2004, Zhang & Paria 2006. Female mice were mated with fertile male to induce pregnancy (day 1 of pregnancyZvaginal plug; Paria et al 1993, Zhang & Paria 2006.…”
Section: Animal and Tissue Preparationmentioning
confidence: 99%
“…The preparation of a receptive uterus for supporting embryo implantation in mice and rats is achieved by sequential effects of ovarian progesterone (P 4 ) and estrogen (E; Yoshinaga & Adams 1966, Psychoyos 1973, Paria et al 1993. However, uterine receptivity is regulated only by ovarian P 4 in hamsters (Prasad et al 1960, Orsini & Meyer 1962, Harper et al 1969, Wang et al 2002, 2004, Zhang & Paria 2006. Studies in the mouse, rat, and agricultural species suggest that cytokines and growth factors produced by the uterine cells in response to ovarian steroids help in preimplantation embryo development and implantation (Carson et al 2000, Modric et al 2000.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation